Overview of Cellular Aspects of the Nervous System: A Narrative Literature Review - Surbakti, Khairul (Phlox Institute: Indonesian Medical Research Organization, 2023)
The structure of neurons varies so much that each neuron is adapted to perform a specific function. Although their functions may vary slightly, neurons have three common components, namely the cell body (soma), dendrites (thin branching fibers from the cell), and the axon. This literature review aimed to describe the cellular aspect of the system nerves in the human body. The cellular constituents of a typical neuron include microtubules (transporters within the cell), neurofibrils (thin supporting fibers extending throughout the neuron), microfilaments (proteins thought to be involved in the transport of cellular products), and Nissl bodies (endoplasmic reticulum and ribosomes). Involved in protein synthesis. Although most neurons are non-dividing cells, some continue to divide after birth; for example, the olfactory neurons in the nose continue to divide throughout life. In conclusion, there are two basic types of cells comprising nervous tissue: neurons and supporting neuroglia. Neurons are electrically excitable cells and transmit electrical or chemical information between other neurons or to effector organs. Neuroglial cells provide structural support, protection, and nutrition for neurons and facilitate neurotransmission.